2021
DOI: 10.3171/2020.10.spine201383
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific template-guided versus standard freehand lumbar pedicle screw implantation: a randomized controlled trial

Abstract: OBJECTIVE Patient-specific template-guided (TG) pedicle screw placement currently achieves the highest reported accuracy in cadaveric and early clinical studies, with reports of reduced use of radiation and less surgical time. However, a clinical randomized controlled trial (RCT) eliminating potential biases is lacking. This study compares TG and standard freehand (FH) pedicle screw insertion techniques in an RCT. METHODS Twenty-four patients (mean age 64 years, 9 men and 15 women) scheduled consecutively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…However, the additional time, the radiation exposure and the high cost for installation and maintenance, required space and personnel for operation, must be considered [ 12 , 26 , 32 ]. In this context the use of a patient specific screw placement guide with a preplanned screw trajectory has been considered as a promising approach [ 6 , 15 , 19 – 21 , 31 , 35 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the additional time, the radiation exposure and the high cost for installation and maintenance, required space and personnel for operation, must be considered [ 12 , 26 , 32 ]. In this context the use of a patient specific screw placement guide with a preplanned screw trajectory has been considered as a promising approach [ 6 , 15 , 19 – 21 , 31 , 35 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the medical literature, accuracy has been determined using specialized software that measures surface deviation, 32 but a grading system is also still used as a sole assessment of accuracy. 33 34 After taking the above in consideration, we adopted the grading system used by Chen and colleagues, which determines the ratio of the screw diameter to the implant corridor width. The overall accuracy in our study was lower compared with previous studies, which can be explained by the variety of study designs and a stricter grading system used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…10 On the contrary, a randomized controlled study of 24 cases with lumbar pedicle screw implantation by Spirig et al reported that radiation exposure was 67% lower in the template-guided technique when compared with the freehand technique, with no significant difference in screw accuracy, operative time, and blood loss, which were inconsistent with the results of the present study. 11 This discrepancy might be due to two reasons as they mentioned: (1) the use of simple screw trajectory by highly experienced surgeons and (2) need for extensive dissection and meticulous removal of soft tissue to ensure proper fit of the template. In contrast to template guide for standard pedicle screw trajectory with convergent drill tubes, CBT template guide with divergent drill tubes is theoretically low profile and can be easily installed without additional surgical exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-specific template guide technique for pedicle screw insertion has reportedly not only improved screw placement accuracy, but also reduced operative time, screw placement time, blood loss, and intraoperative radiation exposure, compared to freehand fluoroscopic-assisted technique. [9][10][11] With regard to the template-guided CBT technique, cadaveric and clinical studies have reported highly accurate screw placement ranging from 2.5% to 9.4% without any cortical breach. [12][13][14][15][16] However, there is no study that can compare it to the standard technique, and little is known about its practical impact.…”
Section: Introductionmentioning
confidence: 99%